HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT DENGAN MINAT MASYARAKAT DALAM MENGIKUTI SENAM KESEHATAN JASMANI DI DUSUN SENDEN 2 SELOMARTANI KALASAN YOGYAKARTA - I Komang Yulitridana; Andri Purwandari; Haerul Anwar (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2017)
Background: Health is a prosperous state physically, mentally and socially, not simply does not  have a disease. It is important for the society to always stay healthy. One of several ways to stay healthy is by doing exercises regularly. Some of the society does not realize the importance of physical exercises for their bodies. Therefore, the society interest needs to be improved in order to stay healthy.Objective: To find out the relationship between society knowledge level and society interest in joining physical exercises in Senden 2 Selomartani Kalasan Yogyakarta.Method: This is a quantitative research. The method used in this study is analytical descriptive and uses cross sectional approach. The population of the research is adult to elderly people who live in Senden 2 Selomartani Kalasan Yogyakarta. The data collection technique used is purposive sampling, with total 84 people. The data collection instrument is questioners and to analyze the data uses Kendall’s tau. Results: The result of this study shows that the analysis bivariate value using kendall’s tau formulation shows that the knowledge level is fairly related to society interest in joining physical exercises r=0,412 with significance of 0,000 (p<0,05).Conclusion: There is a relationship between society knowledge level and society interest in joining physical exercises in Senden 2 Selomartani Kalasan Yogyakarta.